"Hello! This is Jerusalem calling": The revival of spoken Hebrew on the Mandatory radio (1936–1948). Issue 4 (1st October 2016) - Liebes, Tamar; Kampf, Zohar
ABSTRACT: In this article we argue that an important landmark in the revival of spoken Hebrew has been overlooked by historians, linguists, and culture scholars: The launching of Kol Yerushalayim, the Hebrew Service of British Mandatory Radio, on 30 March 1936. Between 1936 and 1948 the Hebrew Hour became the shared public space in which spoken Hebrew – dynamic, updated, meticulously pronounced – was realized. The important role of the Hebrew radio in the Yishuv can be attributed to five factors that were responsible for the spread of spoken Hebrew among both veterans and newcomers: (1) its ability to reach into listeners' homes, which served as a metonym for the yet-absent Zionist sovereignty, creating a shared, exclusive Hebrew space; (2) its contribution to the standardization of Hebrew by adopting the Sephardic accent; (3) its enrichment and updating of the language by inventing and suggesting vital neologisms; (4) its institutionalization of regular time-slots for teaching the language; (5) its innovative ways of addressing audiences, who were simultaneously far away and very close, in accordance with the characteristics of the new medium.